Actor & Avatar : A Scientific and Artistic Catalog - Dieter Mersch; Anton Rey; Thomas Grunwald; Jörg Sternagel; Lorena Kegel; Miriam Laura Loertscher (transcript, 2023)
What kind of relationship do we have with artificial beings (avatars, puppets, robots, etc.)? What does it mean to mirror ourselves in them, to perform them or to play trial identity games with them? Actor & Avatar addresses these questions from artistic and scholarly angles. Contributions on the making of »technical others« and philosophical reflections on artificial alterity are flanked by neuroscientific studies on different ways of perceiving living persons and artificial counterparts. The contributors have achieved a successful artistic-scientific collaboration with extensive visual material.